Sport and entrepreneurship: Having fun while gaining profit / Nor Alwani Omar - Omar, Nor Alwani (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2020)
Fitness and exercise are very important to our body especially students. due to that reason, the mathematical sciences club (persik) had organised a programme called "persik fun day" to give a chance for the students to exercise together and at the same time promote a healthy lifestyle. This programme was held on october 19, 2019 with the involvement of more than 200 students of diploma in mathematical sciences.